Prospective Clinical and Radiologic Evaluation of Patellofemoral Matrix-Induced Autologous Chondrocyte Implantation - Ebert, J.; Fallon, M.; Smith, Anne; Janes, G.; Wood, D. (2015)
Background: While matrix-induced autologous chondrocyte implantation (MACI) has demonstrated encouraging outcomes in the treatment of knee chondral defects, there remains little available research specifically investigating its use in the patellofemoral joint. Purpose: To prospectively evaluate the clinical and radiologic outcome of MACI in the patellofemoral joint. Study Design: Case series; Level of evidence, 4. Methods: In 47 consecutive patients undergoing patellofemoral MACI, clinical (Knee injury and Osteoarthritis Outcome Score, 36-Item Short Form Health Survey, visual analog scale for pain, 6-minute walk test, knee range of motion, and strength assessment) and magnetic resonance imaging (MRI) assessments were undertaken before and 3, 12, and 24 months after surgery. The MRI was performed to assess graft infill and determine an overall MRI composite score. Results were analyzed according to (1) the patient sample overall and (2) after stratification into 4 subgroups per implant location (patella or trochlea) as well as whether or not adjunct tibial tubercle transfer for patellofemoral malalignment was required. Results: The overall patient sample, as well as each of the 4 procedural subgroups, demonstrated clinically and statistically significant (P < .05) improvements over time for all clinical scores. Graft infill and the MRI composite score also demonstrated statistically significant (P < .05) improvements over time, with no evidence of a main effect for procedure group or interaction between procedure group and time. At 24 months after surgery, 40.4% (n = 19) of patients exhibited complete graft infill comparable with the adjacent native cartilage, with a further 6.4% (n = 3) demonstrating a hypertrophic graft. A further 31.9% (n = 15) of patients exhibited 50% to 100% tissue infill, and 17% (n = 8) demonstrated <50% tissue infill. Two patients (4.3%) demonstrated graft failure. At 24 months after surgery, 85% (n = 40) of patients were satisfied with the results of their MACI surgery. Conclusion: These results demonstrate that MACI provides improved clinical and radiologic outcomes to 24 months in patients undergoing treatment specifically for articular cartilage defects on the patella or trochlea, with and without concurrent realignment of the extensor mechanism if required.